(untitled) (Discourse of Law and Administration, 2021)
The concept presented in the draft act of 14 December 2020 amending the Code of Civil Procedure and certain other acts, based on the obligation to include mediation clauses in employment contracts and the introduction of obligatory pre-trial mediation proceedings, was classified as an attempt to introduce obligatory mediation into the Polish legal system. Legal solution regarding mediation containing mandatory elements are not only approved in the doctrine, but also allowed in legal regulations. An important example is the 2008/52/EC European Parliament and of the Council of 25 May 2008 on certain aspects of mediation in civil and commercial matters, the provisions of which do not preclude the obligation on the parties to mediate by national legislation. However, the introduction of obligatory mediation must not interfere with the exercise of a party’s right to access to justice. In the present shape, the proposed solutions threaten the right of the party to a court. This threat manifests itself mainly in the lack of statutory impact of the initiation of mediation on the course of time limits for pursuing claims qualified as tight deadlines and in the absence of expected solutions for the financing of obligatory mediation. Also the reference to Art. 130 of the Code of Civil Procedure if the plaintiff does not attach a document confirming participation in mediation, it is not correct, as the statutory requirement to conduct compulsory pre-litigation proceedings before instituting an action is not related to the issue of the formal conditions of the claim, but to the temporary inadmissibility of court proceedings. Therefore, a more appropriate solution would be for the court to refer the parties to mediation in the event that a compulsory mediation attempt is not made, free of charge for the parties, and it should not be automatic, but after an assessment of the admissibility of a settlement and contraindications to mediation.